Ti3C2Tx-coated NiFe2O4 and preparation method of self-repairing noise-reducing anti-corrosion coating of Ti3C2Tx-coated NiFe2O4

By combining hydrothermal synthesis of Ti3C2Tx@NiFe2O4 composite material with polyurethane matrix, a noise reduction and anti-corrosion coating with self-healing performance was prepared, which solved the problem of easy damage to traditional coatings and achieved efficient noise reduction and anti-corrosion effects.

CN119875490APending Publication Date: 2025-04-25OCEAN UNIV OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510118657.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Traditional noise reduction coatings are prone to damage due to scratches, wear or environmental factors during use, especially in marine environments, and it is difficult to maintain anti-corrosion performance and service life.

Method used

Ti3C2Tx@NiFe2O4 composite material was synthesized by hydrothermal synthesis method to form heterogeneous materials with sandwich structure, and combined with polyurethane matrix to prepare a noise-reducing and anti-corrosion coating with self-healing properties.

Benefits of technology

The coating can be self-healed under light and thermal conditions, improves corrosion resistance and noise reduction, extends service life, and shows good corrosion resistance in marine environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875490A_ABST
    Figure CN119875490A_ABST
Patent Text Reader

Abstract

The invention discloses Ti3C2Tx-coated NiFe2O4 and a preparation method of a self-repairing noise-reducing anticorrosive coating of the Ti3C2Tx-coated NiFe2O4. According to the invention, Ti < 3 > C < 2 > T < x > is prepared by adopting an acid etching method, and Ti < 3 > C < 2 > T < x >-coated NiFe2O4 with a sandwich structure is subsequently synthesized by adopting a hydrothermal synthesis method. Wherein the Ti < 3 > C < 2 > T < x > and the Ni < 2 > O < 4 > are matched according to the mass ratio of (0.1-0.5): 1. Polyester glycol, diisocyanate and disulfide are used as raw materials, addition polymerization is performed according to the molar ratio of 1: (1.25-2): (0.25-1) to prepare a polyurethane matrix, the mass ratio of Ti3C2Tx-coated NiFe2O4 to the polyurethane matrix is (0.01-0.05): 1, and key process parameters such as reaction solvent, temperature and time are optimized. Chemical bonds such as disulfide bonds are introduced, so that the coating is endowed with excellent self-repairing performance, and meanwhile, the noise reduction capability and the long-acting anti-corrosion effect of the coating are remarkably enhanced. The Ti < 3 > C < 2 > T < x >-Ni < 2 > O < 4 > reinforced polyurethane prepared by the invention provides a brand-new design thought and a technical path for the field of self-repairing noise-reducing anti-corrosion materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of synthesis of inorganic materials and polymer material organic coatings, and in particular to a Ti 3 C 2 T x @NiFe 2 O 4 And a preparation method of a self-repairing noise-reducing and anti-corrosion coating. Background Art

[0002] With the acceleration of industrialization and urbanization, noise pollution has become a global environmental problem, seriously affecting people's quality of life and physical and mental health. As an effective means of noise control, noise reduction coatings have been widely used in many industries such as automobiles, oceans, home appliances, pipeline engineering and industrial machinery due to their advantages such as high efficiency, economy and easy construction. However, traditional noise reduction coatings are easily damaged by scratches, wear or environmental factors during use, especially in marine environments, where they will be gradually penetrated by corrosive media in the marine atmosphere or seawater, thereby reducing their anti-corrosion performance and service life. Therefore, the research and development of self-healing anti-corrosion coatings that can repair damage after being damaged has become one of the frontier research hotspots.

[0003] By integrating photothermal materials, photothermal self-healing coatings can trigger self-healing mechanisms under illumination conditions to restore the integrity and protective properties of the coating. Although research on photothermal self-healing coatings has made important progress, it still faces some challenges. Future research should focus on the following directions: optimizing the structure and properties of photothermal materials to further improve the photothermal conversion efficiency; developing low-cost, high-stability preparation processes to achieve the industrial application of photothermal self-healing coatings; combining multiple repair mechanisms to improve the self-healing efficiency and long-term protective capabilities of the coating. Therefore, it is urgent to invent an anti-corrosion organic coating based on photothermal fillers with excellent photothermal self-healing properties and noise reduction properties.

[0004] Here, we propose a novel photothermal filler that is different from any previously reported one. 3 C 2 T x and semiconductor material NiFe 2 O 4 The composite material forms a heterogeneous structure, which can effectively separate photogenerated carriers and prolong their relaxation time, thereby improving the photothermal conversion efficiency. Due to its special microstructure, this composite material can increase the friction between the molecular chains inside the coating. When sound waves enter the material, the air molecules are subjected to friction and adhesion resistance, causing the air to vibrate, thereby converting sound energy into mechanical energy, which is finally converted into heat energy due to friction and dissipated. Summary of the invention

[0006] According to the shortcomings of the prior art, the present invention provides a Ti 3 C 2 T x @NiFe 2 O 4 The simple hydrothermal synthesis method of the present invention mainly has the following innovations:

[0007] 1. Ti synthesized by the present invention 3 C 2 T x @NiFe 2 O 4 With sandwich structure, NiFe 2 O 4 For the core clamped in Ti 3 C 2 T x In the layer, NiFe 2 O 4 The internal cavity improves impedance matching and increases the reflection and scattering of sound waves inside the material. 3 C 2 T x The layered structure can increase the friction between the matrix and the filler, and between the fillers to enhance the viscous loss, thereby improving the damping and noise reduction performance.

[0008] 2. The present invention solves the problem of poor photothermal conversion performance of semiconductor photothermal materials due to low utilization rate of photogenerated electrons and holes and low transmission efficiency of photogenerated electrons by constructing a heterostructure.

[0009] 3. By introducing other covalent bonds such as dynamic disulfide bonds, the polyurethane matrix is ​​provided with self-healing properties, which improves the long-term anti-corrosion performance of the coating. At the same time, the breaking and recombination of disulfide bonds drives the movement of molecular chains, improving the damping and noise reduction performance of the coating.

[0010] In order to achieve the above technical objectives, the present invention is implemented by the following technical means:

[0011] 1. The present invention provides a Ti 3 C 2 T x @NiFe 2 O 4 And its self-repairing noise reduction and anti-corrosion coating, the coating is composed of Ti 3 C 2 T x @NiFe 2 O 4 The composite material and the polyurethane matrix are mixed in a mass ratio of 0.01-0.05:1;

[0012] Among them, Ti 3 C 2 Tx @NiFe 2 O 4 The composite material has a sandwich structure consisting of Ti 3 C 2 T x and NiFe 2 O 4 Synthesize according to a mass ratio of 0.1-0.5:1;

[0013] The polyurethane matrix is ​​prepared by addition polymerization of polyester diol, diisocyanate and disulfide in a molar ratio of 1:1.25-2:0.25-1.

[0014] 2. The present invention further provides a Ti 3 C 2 T x @NiFe 2 O 4 And the preparation method of the self-repairing anti-corrosion coating, the specific implementation steps are as follows:

[0015] 1) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Synthesize Ti at a mass ratio of 0.1-0.5:1 3 C 2 T x @NiFe 2 O 4 Composite materials, in the following order:

[0016] 1.1) Ti 3 C 2 T x Synthesis: Ti was synthesized by acid etching method 3 C 2 T x , the order is:

[0017] 1.1.1) Add 1.5 g lithium fluoride to 20 ml hydrochloric acid solution and stir at room temperature at a speed of 200-800 rpm for 10-30 minutes;

[0018] ——————————————————————————————————1.1.2) In a 40℃ water bath, 1g Ti 3 AlC 2 The powder is slowly added to the above solution and stirred continuously for 24-72 hours;

[0019] 1.1.3) The reaction solution was centrifuged at 3500 rpm with deionized water to collect the precipitate, and this process was repeated until the pH value of the supernatant was close to 7.0. Finally, Ti was obtained by freeze drying for 24 h. 3 C 2 T x ;

[0020] 1.2) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized by hydrothermal reaction at a mass ratio of 0.1-0.5:1 3 C 2 T x @NiFe 2 O 4 , specifically:

[0021] 1.2.1) Weigh Ti in proportion 3 C 2 T x Ultrasonic dispersion into 60 ml of deionized water to form a uniform solution;

[0022] 1.2.2) Weigh nickel nitrate hexahydrate, ferric nitrate nonahydrate and glucose in proportion and add them to the above solution, stir at a speed of 200-800 rpm for 5-30 minutes, transfer to a polytetrafluoroethylene-lined autoclave and keep it in a temperature range of 140-200°C for 9-18 hours, wash it with deionized water and ethanol several times, and vacuum dry it at 60°C for 12 hours;

[0023] 2) Synthesis of polyurethane matrix: Weigh polyester diol, diisocyanate and disulfide in a molar ratio of 1:1.25-2:0.25-1. The specific operation steps are as follows:

[0024] 2.1) Add polyester diol into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture;

[0025] 2.2) Cool down to 70°C, add the solvent, diisocyanate and catalyst dropwise into the three-necked flask, and stir at 300-800 rpm for 1-3 hours;

[0026] 2.3) Raise the temperature to 80°C, dissolve the disulfide in the solvent, ultrasonicate for 5-10 minutes, then add dropwise to the three-necked flask, and continue stirring at 300-800 rpm for 3-6 hours;

[0027] 3) Preparation of self-repairing noise reduction and anti-corrosion coating: According to Ti 3 C 2 T x @NiFe 2 O 4 The mass ratio of Ti to polyurethane matrix is ​​0.01-0.05:1. 3 C 2 T x @NiFe 2 O 4 Add into the above polyurethane system and stir with a mechanical stirrer for 0.5-2 hours.

[0028] Optionally, the polyester diol is any one or more of polybutylene adipate, polyethylene adipate, polycarbonate diol, and polycaprolactone diol;

[0029] Optionally, the diisocyanate is any one or more of toluene diisocyanate, isophorone diisocyanate, hexanediol diisocyanate, dicyclohexylmethane diisocyanate, diphenylmethane diisocyanate, and hexamethylene diisocyanate;

[0030] Optionally, the disulfide is any one or more of bis(2-hydroxyethyl) disulfide, bis(10-hydroxydecyl) disulfide, 4,4'-diaminodiphenyl disulfide, bis(11-hydroxyundecyl) disulfide, bis(4-(hydroxymethyl)phenyl) disulfide, and diallyl disulfide;

[0031] Optionally, the solvent is any one of tetrahydrofuran, acetone, dichloromethane, toluene, dimethylformamide, ether, and dimethylacetamide;

[0032] Optionally, the catalyst is any one of dibutyltin dilaurate, dibutyltin, tetrabutyltin, stannous octoate, and tributyltin chloride.

[0033] 2. The present invention also provides a Ti 3 C 2 T x @NiFe 2 O 4 And the application of the self-repairing noise reduction anti-corrosion coating, the above-synthesized self-repairing anti-corrosion coating is coated on a metal substrate, cured at 60°C for 12-24 hours, cooled to ambient temperature to finally obtain an anti-corrosion organic coating.

[0034] A Ti of the present invention 3 C 2 T x @NiFe 2 O 4 The beneficial effects of the preparation method of the self-repairing noise reduction and anti-corrosion coating compared with the prior art are:

[0035] 1. Ti synthesized by the present invention 3 C 2 T x @NiFe 2 O 4 With sandwich structure, NiFe 2 O 4 For the core clamped in Ti 3 C 2 T x In the layer, NiFe 2 O 4 The internal cavity improves impedance matching and increases the reflection and scattering of sound waves inside the material. 3 C 2 T x The layered structure can increase the friction between the matrix and the filler, and between the fillers to enhance the viscous loss, thereby improving the damping and noise reduction performance.

[0036] 2. The present invention solves the problem of poor photothermal conversion performance of semiconductor photothermal materials due to low utilization rate of photogenerated electrons and holes and low transmission efficiency of photogenerated electrons by constructing a heterostructure.

[0037] 3. The present invention introduces dynamic disulfide bonds into the polyurethane matrix, and uses dynamic disulfide bonds and reversible hydrogen bonds to provide self-repairing properties for the polyurethane matrix, thereby improving the long-term anti-corrosion performance of the coating. The breaking and recombination of the reversible dynamic bonds can drive the movement of the polyurethane molecular chains, increase the friction between the molecular chains, and improve the coating's ability to dissipate sound.

[0038] 4. Experiments have shown that the Ti 3 C 2 T x @NiFe 2 O 4 , combined with a polyurethane substrate to form a composite coating, which exhibits excellent noise reduction capabilities and has the characteristics of multiple-cycle photothermal self-repairing, effectively overcoming the problem that traditional coatings are difficult to provide long-term protection, and showing great development potential and commercial value in the field of marine anti-corrosion coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The Ti synthesized in Example 13 C 2 T x @NiFe 2 O 4 SEM images of

[0041] Figure 2 The Ti synthesized in Example 2 3 C 2 T x @NiFe 2 O 4 SEM images of

[0042] Figure 3 The Ti synthesized in Example 2 3 C 2 T x @NiFe 2 O 4 XRD pattern of

[0043] Figure 4 The Ti synthesized in Example 3 3 C 2 T x @NiFe 2 O 4 SEM images of

[0044] Figure 5 is a stress-strain curve diagram of the synthetic coating of Example 4;

[0045] Figure 6 is a stress-strain curve diagram of the synthetic coating of Example 5;

[0046] Figure 7 is a stress-strain curve diagram of the synthetic coating of Example 6;

[0047] Figure 8 is a stress-strain curve diagram of the synthetic coating of Example 7;

[0048] Fig. 9 The temperature rise curve of the coating synthesized in Example 8 within 180 seconds of near-infrared laser irradiation with a power of 1.5 W and a wavelength of 808 nm and the infrared thermal imaging image after irradiation for 180 seconds;

[0049] Fig.10 This is an optical photograph of the damaged coating and the repaired coating after the coating synthesized in Example 8 was irradiated with a near-infrared laser with a power of 1.5 W and a wavelength of 808 nm for 180 seconds;

[0050] Fig.11 The temperature rise curve of the coating synthesized in Example 9 within 180 seconds of irradiation with a near-infrared laser having a power of 1.5 W and a wavelength of 808 nm and the infrared thermal imaging image after irradiation for 180 seconds;

[0051] Fig.12 These are optical photographs of the damaged coating and the repaired coating after the coating synthesized in Example 9 was irradiated with a near-infrared laser with a power of 1.5 W and a wavelength of 808 nm for 180 seconds;

[0052] Fig.13 These are the Nyquist analysis test results of the electrodes modified with different coatings synthesized in Example 10 after being immersed for 60 days;

[0053] Fig.14 The Bode amplitude analysis test results of the electrodes modified with different coatings synthesized in Example 10 after immersion for 60 days;

[0054] Fig.15 The Bode phase angle analysis test results of the electrodes modified with different coatings synthesized in Example 10 after immersion for 60 days;

[0055] Fig.16 This is a test chart of the noise reduction capability of the coating synthesized in Example 10 in a laboratory environment;

[0056] Fig.17 This is a test chart of the noise reduction ability of the coating synthesized in Example 10 after five scratch-healing experiments. DETAILED DESCRIPTION

[0058] The present invention is described in detail below in conjunction with the accompanying drawings and specific implementation methods so that those skilled in the art can understand and implement the invention. Obviously, the embodiments described below are only some of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0059] The present invention provides a Ti 3 C 2 T x @NiFe 2 O 4 And its self-repairing noise reduction and anti-corrosion coating, the coating is composed of Ti 3 C 2 T x @NiFe 2 O 4 The composite material and the polyurethane matrix are mixed in a mass ratio of 0.01-0.05:1;

[0060] Among them, Ti 3 C 2 T x @NiFe 2 O 4 The composite material has a sandwich structure consisting of Ti 3 C 2T x and NiFe 2 O 4 Synthesize according to a mass ratio of 0.1-0.5:1;

[0061] The polyurethane matrix is ​​prepared by addition polymerization of polyester diol, diisocyanate and disulfide in a molar ratio of 1:1.25-2:0.25-1.

[0062] The present invention further provides a Ti 3 C 2 T x @NiFe 2 O 4 And the preparation method of the self-repairing anti-corrosion coating, the specific implementation steps are as follows:

[0063] 1) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Synthesize Ti at a mass ratio of 0.1-0.5:1 3 C 2 T x @NiFe 2 O 4 Composite materials, in the following order:

[0064] 1.1) Ti 3 C 2 T x Synthesis: Ti was synthesized by acid etching method 3 C 2 T x , the order is:

[0065] 1.1.1) Add 1.5 g lithium fluoride to 20 ml hydrochloric acid solution and stir at room temperature at a speed of 200-800 rpm for 10-30 minutes;

[0066] 1.1.2) In a 40℃ water bath, 1g Ti 3 AlC 2 The powder is slowly added to the above solution and stirred continuously for 24-72 hours;

[0067] 1.1.3) The reaction solution was centrifuged at 3500 rpm with deionized water to collect the precipitate, and this process was repeated until the pH value of the supernatant was close to 7.0. Finally, Ti was obtained by freeze drying for 24 h. 3 C2 T x ;

[0068] 1.2) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized by hydrothermal reaction at a mass ratio of 0.1-0.5:1 3 C 2 T x @NiFe 2 O 4 , specifically:

[0069] 1.2.1) Weigh Ti in proportion 3 C 2 T x Ultrasonic disperse into 60 ml of deionized water to form a uniform solution;

[0070] 1.2.2) Weigh nickel nitrate hexahydrate, ferric nitrate nonahydrate and glucose in proportion and add them to the above solution, stir at a speed of 200-800 rpm for 5-30 minutes, transfer to a polytetrafluoroethylene-lined autoclave and keep it in a temperature range of 140-200°C for 9-18 hours, wash it with deionized water and ethanol several times, and vacuum dry it at 60°C for 12 hours;

[0071] 2) Synthesis of polyurethane matrix: Weigh polyester diol, diisocyanate and disulfide in a molar ratio of 1:1.25-2:0.25-1. The specific operation steps are as follows:

[0072] 2.1) Add polyester diol into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture;

[0073] 2.2) Cool down to 70°C, add the solvent, diisocyanate and catalyst dropwise into the three-necked flask, and stir at 300-800 rpm for 1-3 hours;

[0074] 2.3) Raise the temperature to 80°C, dissolve the disulfide in the solvent, ultrasonicate for 5-10 minutes, then add dropwise to the three-necked flask, and continue stirring at 300-800 rpm for 3-6 hours;

[0075] 3) Preparation of self-repairing noise reduction and anti-corrosion coating: According to Ti 3 C2 T x @NiFe 2 O 4 The mass ratio of Ti to polyurethane matrix is ​​0.01-0.05:1. 3 C 2 T x @NiFe 2 O 4 Add into the above polyurethane system and stir with a mechanical stirrer for 0.5-2 hours.

[0076] Wherein the polyester diol in step 2) is any one or more of polybutylene adipate, polyethylene adipate, polycarbonate diol, and polycaprolactone diol;

[0077] Wherein the diisocyanate in step 2) is any one or more of toluene diisocyanate, isophorone diisocyanate, hexanediol diisocyanate, dicyclohexylmethane diisocyanate, diphenylmethane diisocyanate, and hexamethylene diisocyanate;

[0078] Wherein the disulfide in step 2) is any one or more of bis(2-hydroxyethyl) disulfide, bis(10-hydroxydecyl) disulfide, 4,4'-diaminodiphenyl disulfide, bis(11-hydroxyundecyl) disulfide, bis(4-(hydroxymethyl)phenyl) disulfide, and diallyl disulfide;

[0079] Wherein the solvent in step 2) is any one of tetrahydrofuran, acetone, dichloromethane, toluene, dimethylformamide, ether, and dimethylacetamide;

[0080] The catalyst in step 2) is any one of dibutyltin dilaurate, dibutyltin, tetrabutyltin, stannous octoate and tributyltin chloride.

[0081] ————————————————————————————————Example 1

[0082] The present invention provides a Ti 3 C 2 T x @NiFe 2 O 4 And a preparation method of a self-repairing noise-reducing and anti-corrosion coating, the coating is composed of Ti 3 C 2 T x @NiFe 2 O 4 Mixed with polyurethane matrix, the specific steps are as follows:

[0083] 1) Ti 3 C2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized at a mass ratio of 0.1:1 3 C 2 T x @NiFe 2 O 4 Composite materials, in the following order:

[0084] 1.1) Ti 3 C 2 T x Synthesis: Ti was synthesized by acid etching method 3 C 2 T x , the order is:

[0085] 1.1.1) Add 1.5 g lithium fluoride to 20 ml hydrochloric acid solution and stir at 400 rpm for 10 minutes at room temperature;

[0086] 1.1.2) In a 40℃ water bath, 1g Ti 3 AlC 2 The powder was slowly added to the above solution and stirred continuously for 24 hours;

[0087] 1.1.3) The reaction solution was centrifuged at 3500 rpm with deionized water to collect the precipitate, and this process was repeated until the pH value of the supernatant was close to 7.0. Finally, Ti was obtained by freeze drying for 24 h. 3 C 2 T x ;

[0088] 1.2) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized by hydrothermal reaction at a mass ratio of 0.1:1 3 C 2 T x @NiFe 2 O 4 , specifically:

[0089] 1.2.1) Weigh 0.05g Ti according to the proportion 3 C 2 T x Ultrasonic dispersion into 60 ml of deionized water to form a uniform solution;

[0090] 1.2.2) 0.797 g nickel nitrate hexahydrate, 2.21 g ferric nitrate nonahydrate and 0.328 g glucose were weighed in proportion and added to the above solution, stirred at 300 rpm for 10 minutes, and after mixing evenly, transferred to a polytetrafluoroethylene-lined autoclave and kept at 200°C for 18 hours, washed with deionized water and ethanol several times, and vacuum dried at 60°C for 12 hours;

[0091] 2) Synthesis of polyurethane matrix: polyethylene adipate, isophorone diisocyanate, and 4,4'-diaminodiphenyl disulfide were weighed in a molar ratio of 1:1.25:0.25. The specific operation steps are as follows:

[0092] 2.1) Add 5 g of polyethylene adipate into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture;

[0093] 2.2) Cool to 70°C, add 5 ml of dimethylformamide, 0.69 g of isophorone diisocyanate and 0.5 ml of tetrabutyltin dropwise into a three-necked flask, and stir at 300 rpm for 3 hours;

[0094] 2.3) Raise the temperature to 80°C, dissolve 0.16 g of 4,4'-diaminodiphenyl disulfide in 3 ml of dimethylformamide, treat with ultrasound for 10 minutes, then add dropwise to the three-necked flask, and continue stirring at 300 rpm for 3 hours;

[0095] 3) Preparation of self-repairing noise reduction and anti-corrosion coating: According to Ti 3 C 2 T x @NiFe 2 O 4 The mass ratio of Ti to polyurethane matrix is ​​0.01:1. 3 C 2 T x @NiFe 2 O 4 Add into the above polyurethane system and stir with a mechanical stirrer for 0.5 hour.

[0096] For the Ti obtained above 3 C 2 T x @NiFe 2 O 4Perform characterization tests:

[0097] from Figure 1 It can be seen that Ti 3 C 2 T x With a typical two-dimensional accordion structure, NiFe 2 O 4 It is in the shape of nano hollow spheres. After the two materials are combined together, a large amount of NiFe 2 O 4 Insert into Ti 3 C 2 T x A sandwich structure is formed in the interlayer gaps of the sheets.

[0098] Embodiment 2

[0099] The present invention provides a Ti 3 C 2 T x @NiFe 2 O 4 And a preparation method of a self-repairing noise-reducing and anti-corrosion coating, the coating is composed of Ti 3 C 2 T x @NiFe 2 O 4 Mixed with polyurethane matrix, the specific steps are as follows:

[0100] 1) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized at a mass ratio of 0.3:1 3 C 2 T x @NiFe 2 O 4 Composite materials, in the following order:

[0101] 1.1) Ti 3 C 2 T x Synthesis: Ti was synthesized by acid etching method 3 C 2 T x , the order is:

[0102] 1.1.1) Add 1.5 g lithium fluoride to 20 ml hydrochloric acid solution and stir at 400 rpm for 10 minutes at room temperature;

[0103] 1.1.2) In a 40℃ water bath, 1g Ti 3 AlC 2 The powder was slowly added to the above solution and stirred continuously for 24 hours;

[0104] 1.1.3) The reaction solution was centrifuged at 3500 rpm with deionized water to collect the precipitate, and this process was repeated until the pH value of the supernatant was close to 7.0. Finally, Ti was obtained by freeze drying for 24 h. 3 C 2 T x ;

[0105] 1.2) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized by hydrothermal reaction at a mass ratio of 0.3:1 3 C 2 T x @NiFe 2 O 4 , specifically:

[0106] 1.2.1) Weigh 0.15g Ti according to the proportion 3 C 2 T x Ultrasonic disperse into 60 ml of deionized water to form a uniform solution;

[0107] 1.2.2) 0.797 g nickel nitrate hexahydrate, 2.21 g ferric nitrate nonahydrate and 0.328 g glucose were weighed in proportion and added to the above solution, stirred at 300 rpm for 10 minutes, and after mixing evenly, transferred to a polytetrafluoroethylene-lined autoclave and kept at 180°C for 15 hours, washed with deionized water and ethanol several times, and vacuum dried at 60°C for 12 hours;

[0108] 2) Synthesis of polyurethane matrix: polyethylene adipate, isophorone diisocyanate, and 4,4'-diaminodiphenyl disulfide were weighed in a molar ratio of 1:1.25:0.25. The specific operation steps are as follows:

[0109] 2.1) Add 5 g of polyethylene adipate into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture;

[0110] 2.2) Cool down to 70°C, add 5 ml of dimethylformamide, 0.69 g of isophorone diisocyanate and 0.5 ml of tetrabutyltin into a three-necked flask, and stir at 300 rpm for 3 hours;

[0111] 2.3) Raise the temperature to 80°C, dissolve 0.16 g of 4,4'-diaminodiphenyl disulfide in 3 ml of dimethylformamide, treat with ultrasound for 10 minutes, then add dropwise to the three-necked flask, and continue stirring at 300 rpm for 3 hours;

[0112] 3) Preparation of self-repairing noise reduction and anti-corrosion coating: According to Ti 3 C 2 T x @NiFe 2 O 4 The mass ratio of Ti to polyurethane matrix is ​​0.01:1. 3 C 2 T x @NiFe 2 O 4 Add into the above polyurethane system and stir with a mechanical stirrer for 0.5 hour.

[0113] The two-dimensional porous nano NiFe 2 O 4 Perform characterization tests:

[0114] from Figure 2 It can be seen that Ti 3 C 2 T x With a typical two-dimensional accordion structure, NiFe 2 O 4 It is in the shape of nano hollow spheres. After the two materials are combined together, NiFe 2 O 4 Insert into Ti 3 C 2 T x A sandwich structure is formed in the interlamellar gaps of the sheets. Compared with Example 1, the number of nanospheres between the sheets is slightly less, but the dispersibility is significantly improved.

[0115] from Figure 3 It can be seen that the crystal structure of the obtained material was characterized by XRD diffraction. 3 AlC 2 Transformed into multilayer Ti 3 C 2 T x When the (002) peak shifts to the left, it indicates that Ti 3 AlC 2 Successfully etched into Ti3 C 2 T x .Ti 3 C 2 T x The diffraction peaks at 8.85, 18.20, 27.48 and 35.78 correspond to the (002), (004), (006) and (008) planes, respectively. There are 7 diffraction peaks at 2θ=18.5, 30.2, 35.7, 43.4, 54.0, 57.3 and 62.9, which are NiFe 2 O 4 The reflections of (111), (220), (311), (400), (422), (511) and (440) planes are shown in Figure 2. It can be seen that Ti was successfully synthesized. 3 C 2 T x @NiFe 2 O 4 Composite materials.

[0116] Embodiment 3

[0117] The present invention provides a Ti 3 C 2 T x @NiFe 2 O 4 And a preparation method of a self-repairing noise-reducing and anti-corrosion coating, the coating is composed of Ti 3 C 2 T x @NiFe 2 O 4 Mixed with polyurethane matrix, the specific steps are as follows:

[0118] 1) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized at a mass ratio of 0.5:1 3 C 2 T x @NiFe 2 O 4 Composite materials, in the following order:

[0119] 1.1) Ti 3 C 2 T xSynthesis: Ti was synthesized by acid etching method 3 C 2 T x , the order is:

[0120] 1.1.1) Add 1.5 g lithium fluoride to 20 ml hydrochloric acid solution and stir at 400 rpm for 10 minutes at room temperature;

[0121] 1.1.2) In a 40℃ water bath, 1g Ti 3 AlC 2 The powder was slowly added to the above solution and stirred continuously for 24 hours;

[0122] 1.1.3) The reaction solution was centrifuged at 3500 rpm with deionized water to collect the precipitate, and this process was repeated until the pH value of the supernatant was close to 7.0. Finally, Ti was obtained by freeze drying for 24 h. 3 C 2 T x ;

[0123] 1.2) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized by hydrothermal reaction at a mass ratio of 0.5:1 3 C 2 T x @NiFe 2 O 4 , specifically:

[0124] 1.2.1) Weigh 0.25g Ti according to the proportion 3 C 2 T x Ultrasonic dispersion into 60 ml of deionized water to form a uniform solution;

[0125] 1.2.2) 0.797 g nickel nitrate hexahydrate, 2.21 g ferric nitrate nonahydrate and 0.328 g glucose were weighed in proportion and added to the above solution, stirred at 300 rpm for 10 minutes, and after mixing evenly, transferred to a polytetrafluoroethylene-lined autoclave and kept at 150°C for 12 hours, washed with deionized water and ethanol several times, and vacuum dried at 60°C for 12 hours;

[0126] 2) Synthesis of polyurethane matrix: polyethylene adipate, isophorone diisocyanate, and 4,4'-diaminodiphenyl disulfide were weighed in a molar ratio of 1:1.25:0.25. The specific operation steps are as follows:

[0127] 2.1) Add 5 g of polyethylene adipate into a three-necked flask, heat to 100°C, and draw vacuum for 2 hours to remove water;

[0128] 2.2) Cool down to 70°C, add 5 ml of dimethylformamide, 0.69 g of isophorone diisocyanate and 0.5 ml of tetrabutyltin into a three-necked flask, and stir at 300 rpm for 3 hours;

[0129] 2.3) Raise the temperature to 80°C, dissolve 0.16 g of 4,4'-diaminodiphenyl disulfide in 3 ml of dimethylformamide, treat with ultrasound for 10 minutes, then add dropwise to the three-necked flask, and continue stirring at 300 rpm for 3 hours;

[0130] 3) Preparation of self-repairing noise reduction and anti-corrosion coating: According to Ti 3 C 2 T x @NiFe 2 O 4 The mass ratio of Ti to polyurethane matrix is ​​0.01:1. 3 C 2 T x @NiFe 2 O 4 Add into the above polyurethane system and stir with a mechanical stirrer for 0.5 hour.

[0131] For the Ti obtained above 3 C 2 T x @NiFe 2 O 4 Perform characterization tests:

[0132] like Figure 4 As shown, Ti 3 C 2 T x With a typical two-dimensional accordion structure, NiFe 2 O 4 It is in the shape of nano hollow spheres. After the two materials are combined together, a very small amount of NiFe 2 O 4 Insert into Ti 3 C 2 T x A sandwich structure is formed in the interlayer gaps of the sheets.

[0133] Embodiment 4

[0134] The present invention provides a Ti 3 C 2 T x @NiFe 2 O 4 And a preparation method of a self-repairing noise-reducing and anti-corrosion coating, the coating is composed of Ti 3 C 2 T x @NiFe 2 O 4 Mixed with polyurethane matrix, the specific steps are as follows:

[0135] 1) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized at a mass ratio of 0.3:1 3 C 2 T x @NiFe 2 O 4 Composite materials, in the following order:

[0136] 1.1) Ti 3 C 2 T x Synthesis: Ti was synthesized by acid etching method 3 C 2 T x , the order is:

[0137] 1.1.1) Add 1.5 g lithium fluoride to 20 ml hydrochloric acid solution and stir at 400 rpm for 10 minutes at room temperature;

[0138] 1.1.2) In a 40℃ water bath, 1g Ti 3 AlC 2 The powder was slowly added to the above solution and stirred continuously for 24 hours;

[0139] 1.1.3) The reaction solution was centrifuged at 3500 rpm with deionized water to collect the precipitate, and this process was repeated until the pH value of the supernatant was close to 7.0. Finally, Ti was obtained by freeze drying for 24 h. 3 C 2 T x ;

[0140] 1.2) Ti3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized by hydrothermal reaction in a mass ratio of 0.3:1 3 C 2 T x @NiFe 2 O 4 , specifically:

[0141] 1.2.1) Weigh 0.15g Ti according to the proportion 3 C 2 T x Ultrasonic dispersion into 60 ml of deionized water to form a uniform solution;

[0142] 1.2.2) 0.797 g nickel nitrate hexahydrate, 2.21 g ferric nitrate nonahydrate and 0.328 g glucose were weighed in proportion and added to the above solution, stirred at 300 rpm for 10 minutes, and after mixing evenly, transferred to a polytetrafluoroethylene-lined autoclave and kept at 180°C for 15 hours, washed with deionized water and ethanol several times, and vacuum dried at 60°C for 12 hours;

[0143] 2) Synthesis of polyurethane matrix: polyethylene adipate, isophorone diisocyanate, and 4,4'-diaminodiphenyl disulfide were weighed in a molar ratio of 1:1.25:0.25. The specific operation steps are as follows:

[0144] 2.1) Add 5 g of polyethylene adipate into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture;

[0145] 2.2) Cool down to 70°C, add 5 ml of dimethylformamide, 0.69 g of isophorone diisocyanate and 0.5 ml of tetrabutyltin into a three-necked flask, and stir at 300 rpm for 3 hours;

[0146] 2.3) Raise the temperature to 80°C, dissolve 0.16 g of 4,4'-diaminodiphenyl disulfide in 3 ml of dimethylformamide, treat with ultrasound for 10 minutes, then add dropwise to the three-necked flask, and continue stirring at 300 rpm for 3 hours;

[0147] 3) Preparation of self-repairing noise reduction and anti-corrosion coating: According to Ti 3 C 2 Tx @NiFe 2 O 4 The mass ratio of Ti to polyurethane matrix is ​​0.01:1. 3 C 2 T x @NiFe 2 O 4 Add into the above polyurethane system and stir with a mechanical stirrer for 0.5 hour.

[0148] The performance of the organic coating obtained above was tested:

[0149] Depend on Figure 5 The mechanical properties of the coating were tested through tensile tests. The tensile strength of the coating reached 1.84MPa and the elongation at break reached 576%, showing good mechanical properties.

[0150] Embodiment 5

[0151] The present invention provides a Ti 3 C 2 T x @NiFe 2 O 4 And a preparation method of a self-repairing noise-reducing and anti-corrosion coating, the coating is composed of Ti 3 C 2 T x @NiFe 2 O 4 Mixed with polyurethane matrix, the specific steps are as follows:

[0152] 1) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 According to the mass ratio of 0.3:1, Ti was synthesized 3 C 2 T x @NiFe 2 O 4 Composite materials, in the following order:

[0153] 1.1) Ti 3 C 2 T x Synthesis: Ti was synthesized by acid etching method 3 C 2 Tx , the order is:

[0154] 1.1.1) Add 1.5 g lithium fluoride to 20 ml hydrochloric acid solution and stir at 400 rpm for 10 minutes at room temperature;

[0155] 1.1.2) In a 40℃ water bath, 1g Ti 3 AlC 2 The powder was slowly added to the above solution and stirred continuously for 24 hours;

[0156] 1.1.3) The reaction solution was centrifuged at 3500 rpm with deionized water to collect the precipitate, and this process was repeated until the pH value of the supernatant was close to 7.0. Finally, Ti was obtained by freeze drying for 24 h. 3 C 2 T x ;

[0157] 1.2) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized by hydrothermal reaction at a mass ratio of 0.3:1 3 C 2 T x @NiFe 2 O 4 , specifically:

[0158] 1.2.1) Weigh 0.15g Ti according to the proportion 3 C 2 T x Ultrasonic dispersion into 60 ml of deionized water to form a uniform solution;

[0159] 1.2.2) 0.797 g nickel nitrate hexahydrate, 2.21 g ferric nitrate nonahydrate and 0.328 g glucose were weighed in proportion and added to the above solution, stirred at 300 rpm for 10 minutes, and after mixing evenly, transferred to a polytetrafluoroethylene-lined autoclave and kept at 180°C for 15 hours, washed with deionized water and ethanol several times, and vacuum dried at 60°C for 12 hours;

[0160] 2) Synthesis of polyurethane matrix: polyethylene adipate, isophorone diisocyanate, and 4,4'-diaminodiphenyl disulfide were weighed in a molar ratio of 1:1.5:0.5. The specific steps are as follows:

[0161] 2.1) Add 5 g of polyethylene adipate into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture;

[0162] 2.2) Cool down to 70°C, add 5 ml of dimethylformamide, 0.83 g of isophorone diisocyanate and 0.5 ml of tetrabutyltin into a three-necked flask, and stir at 300 rpm for 3 hours;

[0163] 2.3) Raise the temperature to 80°C, dissolve 0.31 g of 4,4'-diaminodiphenyl disulfide in 3 ml of dimethylformamide, treat with ultrasound for 10 minutes, then add dropwise to the three-necked flask, and continue stirring at 300 rpm for 3 hours;

[0164] 3) Preparation of self-repairing noise reduction and anti-corrosion coating: According to Ti 3 C 2 T x @NiFe 2 O 4 The mass ratio of Ti to polyurethane matrix is ​​0.01:1. 3 C 2 T x @NiFe 2 O 4 Add to the above polyurethane system, stir with a mechanical stirrer for 0.5 hour;

[0165] The performance of the organic coating obtained above was tested:

[0166] Depend on Figure 6 The mechanical properties of the coating were tested by tensile tests. The tensile strength of the coating reached 2.18 MPa and the elongation at break reached 606%, showing good mechanical properties. Compared with Example 4, the mechanical strength and flexibility of the coating were improved.

[0167] Embodiment 6

[0168] The present invention provides a Ti 3 C 2 T x @NiFe 2 O 4 And a preparation method of a self-repairing noise-reducing and anti-corrosion coating, the coating is composed of Ti 3 C 2 T x @NiFe 2 O 4 Mixed with polyurethane matrix, the specific steps are as follows:

[0169] 1) Ti 3 C2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized at a mass ratio of 0.3:1 3 C 2 T x @NiFe 2 O 4 Composite materials, in the following order:

[0170] 1.1) Ti 3 C 2 T x Synthesis: Ti was synthesized by acid etching method 3 C 2 T x , the order is:

[0171] 1.1.1) Add 1.5 g lithium fluoride to 20 ml hydrochloric acid solution and stir at 400 rpm for 10 minutes at room temperature;

[0172] 1.1.2) In a 40℃ water bath, 1g Ti 3 AlC 2 The powder was slowly added to the above solution and stirred continuously for 24 hours;

[0173] 1.1.3) The reaction solution was centrifuged at 3500 rpm with deionized water to collect the precipitate, and this process was repeated until the pH value of the supernatant was close to 7.0. Finally, Ti was obtained by freeze drying for 24 h. 3 C 2 T x ;

[0174] 1.2) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized by hydrothermal reaction at a mass ratio of 0.3:1 3 C 2 T x @NiFe 2 O 4 , specifically:

[0175] 1.2.1) Weigh 0.15g Ti according to the proportion 3 C 2 T x Ultrasonic dispersion into 60 ml of deionized water to form a uniform solution;

[0176] 1.2.2) 0.797 g nickel nitrate hexahydrate, 2.21 g ferric nitrate nonahydrate and 0.328 g glucose were weighed in proportion and added to the above solution, stirred at 300 rpm for 10 minutes, and after mixing evenly, transferred to a polytetrafluoroethylene-lined autoclave and kept at 180°C for 15 hours, washed with deionized water and ethanol several times, and vacuum dried at 60°C for 12 hours;

[0177] 2) Synthesis of polyurethane matrix: polyethylene adipate, isophorone diisocyanate and 4,4'-diaminodiphenyl disulfide were weighed in a molar ratio of 1:1.75:0.75. The specific operation steps are as follows:

[0178] 2.1) Add 5 g of polyethylene adipate into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture;

[0179] 2.2) Cool down to 70°C, add 5 ml of dimethylformamide, 0.97 g of isophorone diisocyanate and 0.5 ml of tetrabutyltin into a three-necked flask, and stir at 300 rpm for 3 hours;

[0180] 2.3) Raise the temperature to 80°C, dissolve 0.47 g of 4,4'-diaminodiphenyl disulfide in 3 ml of dimethylformamide, treat with ultrasound for 10 minutes, then add dropwise to the three-necked flask, and continue stirring at 300 rpm for 3 hours;

[0181] 3) Preparation of self-repairing noise reduction and anti-corrosion coating: According to Ti 3 C 2 T x @NiFe 2 O 4 The mass ratio of Ti to polyurethane matrix is ​​0.01:1. 3 C 2 T x @NiFe 2 O 4 Add to the above polyurethane system and stir with a mechanical stirrer for 0.5 hours;

[0182] The performance of the organic coating obtained above was tested:

[0183] Depend on Figure 7The mechanical properties of the coating were tested by tensile tests. The tensile strength of the coating reached 2.36 MPa, and the elongation at break reached 599%, showing good mechanical properties. Compared with Example 5, the mechanical strength of the coating was significantly improved, and the flexibility was slightly reduced.

[0184] Embodiment 7

[0185] The present invention provides a Ti 3 C 2 T x @NiFe 2 O 4 And a preparation method of a self-repairing noise-reducing and anti-corrosion coating, the coating is composed of Ti 3 C 2 T x @NiFe 2 O 4 Mixed with polyurethane matrix, the specific steps are as follows:

[0186] 1) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized at a mass ratio of 0.3:1 3 C 2 T x @NiFe 2 O 4 Composite materials, in the following order:

[0187] 1.1) Ti 3 C 2 T x Synthesis: Ti was synthesized by acid etching method 3 C 2 T x , the order is:

[0188] 1.1.1) Add 1.5 g lithium fluoride to 20 ml hydrochloric acid solution and stir at 400 rpm for 10 minutes at room temperature;

[0189] 1.1.2) In a 40℃ water bath, 1g Ti 3 AlC 2 The powder was slowly added to the above solution and stirred continuously for 24 hours;

[0190] 1.1.3) The reaction solution was centrifuged at 3500 rpm with deionized water to collect the precipitate, and this process was repeated until the pH value of the supernatant was close to 7.0. Finally, Ti was obtained by freeze drying for 24 h. 3 C 2 T x ;

[0191] 1.2) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized by hydrothermal reaction at a mass ratio of 0.3:1 3 C 2 T x @NiFe 2 O 4 , specifically:

[0192] 1.2.1) Weigh 0.15g Ti according to the proportion 3 C 2 T x Ultrasonic dispersion into 60 ml of deionized water to form a uniform solution;

[0193] 1.2.2) 0.797 g nickel nitrate hexahydrate, 2.21 g ferric nitrate nonahydrate and 0.328 g glucose were weighed in proportion and added to the above solution, stirred at 300 rpm for 10 minutes, and after mixing evenly, transferred to a polytetrafluoroethylene-lined autoclave and kept at 180°C for 15 hours, washed with deionized water and ethanol several times, and vacuum dried at 60°C for 12 hours;

[0194] 2) Synthesis of polyurethane matrix: polyethylene adipate, isophorone diisocyanate, and 4,4'-diaminodiphenyl disulfide were weighed in a molar ratio of 1:2:1. The specific operation steps are as follows:

[0195] 2.1) Add 5 g of polyethylene adipate into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture;

[0196] 2.2) Cool down to 70°C, add 5 ml of dimethylformamide, 1.11 g of isophorone diisocyanate and 0.5 ml of tetrabutyltin into a three-necked flask, and stir at 300 rpm for 3 hours;

[0197] 2.3) Raise the temperature to 80°C, dissolve 0.62 g of 4,4'-diaminodiphenyl disulfide in 3 ml of dimethylformamide, treat with ultrasound for 10 minutes, then add dropwise to the three-necked flask, and continue stirring at 300 rpm for 3 hours;

[0198] 3) Preparation of self-repairing noise reduction and anti-corrosion coating: According to Ti 3 C 2 T x @NiFe 2 O 4 The mass ratio of Ti to polyurethane matrix is ​​0.01:1. 3 C 2 T x @NiFe 2 O 4 Add to the above polyurethane system and stir with a mechanical stirrer for 0.5 hours;

[0199] The performance of the organic coating obtained above was tested:

[0200] Depend on Figure 8 The mechanical properties of the coating were tested by tensile tests. The tensile strength of the coating reached 2.12 MPa and the elongation at break reached 559%, showing good mechanical properties. In many embodiments, the elongation at break was poor.

[0201] Embodiment 8

[0202] ————————————————————————————————The present invention provides a Ti 3 C 2 T x @NiFe 2 O 4 And a preparation method of a self-repairing noise-reducing and anti-corrosion coating, the coating is composed of Ti 3 C 2 T x @NiFe 2 O 4 Mixed with polyurethane matrix, the specific steps are as follows:

[0203] 1) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized at a mass ratio of 0.3:1 3 C 2 Tx @NiFe 2 O 4 Composite materials, in the following order:

[0204] 1.1) Ti 3 C 2 T x Synthesis: Ti was synthesized by acid etching method 3 C 2 T x , the order is:

[0205] 1.1.1) Add 1.5 g lithium fluoride to 20 ml hydrochloric acid solution and stir at 400 rpm for 10 minutes at room temperature;

[0206] 1.1.2) In a 40℃ water bath, 1g Ti 3 AlC 2 The powder was slowly added to the above solution and stirred continuously for 24 hours;

[0207] 1.1.3) The reaction solution was centrifuged at 3500 rpm with deionized water to collect the precipitate, and this process was repeated until the pH value of the supernatant was close to 7.0. Finally, Ti was obtained by freeze drying for 24 h. 3 C 2 T x ;

[0208] 1.2) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized by hydrothermal reaction at a mass ratio of 0.3:1 3 C 2 T x @NiFe 2 O 4 , specifically:

[0209] 1.2.1) Weigh 0.15g Ti according to the proportion 3 C 2 T x Ultrasonic dispersion into 60 ml of deionized water to form a uniform solution;

[0210] 1.2.2) 0.797 g nickel nitrate hexahydrate, 2.21 g ferric nitrate nonahydrate and 0.328 g glucose were weighed in proportion and added to the above solution, stirred at 300 rpm for 10 minutes, and after mixing evenly, transferred to a polytetrafluoroethylene-lined autoclave and kept at 180°C for 15 hours, washed with deionized water and ethanol several times, and vacuum dried at 60°C for 12 hours;

[0211] 2) Synthesis of polyurethane matrix: polyethylene adipate, isophorone diisocyanate, and 4,4'-diaminodiphenyl disulfide were weighed in a molar ratio of 1:1.75:0.75. The specific operation steps are as follows:

[0212] 2.1) Add 5 g of polyethylene adipate into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture;

[0213] 2.2) Cool down to 70°C, add 5 ml of dimethylformamide, 0.97 g of isophorone diisocyanate and 0.5 ml of tetrabutyltin into a three-necked flask, and stir at 300 rpm for 3 hours;

[0214] 2.3) Raise the temperature to 80°C, dissolve 0.47 g of 4,4'-diaminodiphenyl disulfide in 3 ml of dimethylformamide, treat with ultrasound for 10 minutes, then add dropwise to the three-necked flask, and continue stirring at 300 rpm for 3 hours;

[0215] 3) Preparation of self-repairing noise reduction and anti-corrosion coating: According to Ti 3 C 2 T x @NiFe 2 O 4 The mass ratio of Ti to polyurethane matrix is ​​0.01:1. 3 C 2 T x @NiFe 2 O 4 Add to the above polyurethane system and stir with a mechanical stirrer for 0.5 hours;

[0216] The performance of the organic coating obtained above was tested:

[0217] The temperature rise curve of the coating within 180s of 1.5W 808nm NIR laser irradiation and the infrared thermal imaging after 180s of irradiation are shown in the figure below. Fig. 9 As shown, the maximum temperature can reach 55.1℃.

[0218] After the coating was irradiated with 1.5W 808nm NIR laser for 180s, the optical photos of the damaged coating and the repaired coating are as follows: Fig.10 As shown in Figure 3, the coating exhibited a self-healing trend within 180 s, but the scratch was not completely healed within 180 s.

[0219] Embodiment 9

[0220] The present invention provides a Ti 3 C 2 T x @NiFe 2 O 4 And a preparation method of a self-repairing noise-reducing and anti-corrosion coating, the coating is composed of Ti 3 C 2 T x @NiFe 2 O 4 Mixed with polyurethane matrix, the specific steps are as follows:

[0221] 1) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized at a mass ratio of 0.3:1 3 C 2 T x @NiFe 2 O 4 Composite materials, in the following order:

[0222] 1.1) Ti 3 C 2 T x Synthesis: Ti was synthesized by acid etching method 3 C 2 T x , the order is:

[0223] 1.1.1) Add 1.5 g lithium fluoride to 20 ml hydrochloric acid solution and stir at 400 rpm for 10 minutes at room temperature;

[0224] 1.1.2) In a 40℃ water bath, 1g Ti 3 AlC 2 The powder was slowly added to the above solution and stirred continuously for 24 hours;

[0225] 1.1.3) The reaction solution was centrifuged at 3500 rpm with deionized water to collect the precipitate, and this process was repeated until the pH value of the supernatant was close to 7.0. Finally, Ti was obtained by freeze drying for 24 h. 3 C2 T x ;

[0226] 1.2) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized by hydrothermal reaction at a mass ratio of 0.3:1 3 C 2 T x @NiFe 2 O 4 , specifically:

[0227] 1.2.1) Weigh 0.15g Ti according to the proportion 3 C 2 T x Ultrasonic disperse into 60 ml of deionized water to form a uniform solution;

[0228] 1.2.2) 0.797 g nickel nitrate hexahydrate, 2.21 g ferric nitrate nonahydrate and 0.328 g glucose were weighed in proportion and added to the above solution, stirred at 300 rpm for 10 minutes, and after mixing evenly, transferred to a polytetrafluoroethylene-lined autoclave and kept at 180°C for 15 hours, washed with deionized water and ethanol several times, and vacuum dried at 60°C for 12 hours;

[0229] 2) Synthesis of polyurethane matrix: polyethylene adipate, isophorone diisocyanate, and 4,4'-diaminodiphenyl disulfide were weighed in a molar ratio of 1:1.75:0.75. The specific operation steps are as follows:

[0230] 2.1) Add 5 g of polyethylene adipate into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture;

[0231] 2.2) Cool down to 70°C, add 5 ml of dimethylformamide, 0.97 g of isophorone diisocyanate and 0.5 ml of tetrabutyltin into a three-necked flask, and stir at 300 rpm for 3 hours;

[0232] 2.3) Raise the temperature to 80°C, dissolve 0.47 g of 4,4'-diaminodiphenyl disulfide in 3 ml of dimethylformamide, treat with ultrasound for 10 minutes, then add dropwise to the three-necked flask, and continue stirring at 300 rpm for 3 hours;

[0233] 3) Preparation of self-repairing noise reduction and anti-corrosion coating: According to Ti 3 C 2 T x @NiFe 2 O 4 The mass ratio of Ti to polyurethane matrix is ​​0.03:1. 3 C 2 T x @NiFe 2 O 4 Add to the above polyurethane system and stir with a mechanical stirrer for 0.5 hours;

[0234] The performance of the organic coating obtained above was tested:

[0235] The temperature rise curve of the coating within 180s of 1.5W 808nm NIR laser irradiation and the infrared thermal imaging after 180s of irradiation are shown in the figure below. Fig.11 As shown, the highest temperature can reach 70.9℃, showing good photothermal conversion performance.

[0236] After the prepared coating was irradiated with 1.5W 808nm NIR laser for 180s, the optical photos of the damaged coating and the repaired coating are as follows: Fig.12 As shown in Figure 2, the coating exhibited good self-healing performance within 180s. 3 C 2 T x @NiFe 2 O 4 After NIR laser irradiation, the light is converted into heat, and the coating is locally heated to trigger the reconstruction of dynamic disulfide bonds and reversible hydrogen bonds to repair scratches on the coating.

[0237] Embodiment 10

[0238] ————————————————————————————————The present invention provides a Ti 3 C 2 T x @NiFe 2 O 4 And a preparation method of a self-repairing noise-reducing and anti-corrosion coating, the coating is composed of Ti 3 C 2 T x @NiFe 2 O 4 Mixed with polyurethane matrix, the specific steps are as follows:

[0239] 1) Ti 3 C 2 T x @NiFe 2 O4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized at a mass ratio of 0.3:1 3 C 2 T x @NiFe 2 O 4 Composite materials, in the following order:

[0240] 1.1) Ti 3 C 2 T x Synthesis: Ti was synthesized by acid etching method 3 C 2 T x , the order is:

[0241] 1.1.1) Add 1.5 g lithium fluoride to 20 ml hydrochloric acid solution and stir at 400 rpm for 10 minutes at room temperature;

[0242] 1.1.2) In a 40℃ water bath, 1g Ti 3 AlC 2 The powder was slowly added to the above solution and stirred continuously for 24 hours;

[0243] 1.1.3) The reaction solution was centrifuged at 3500 rpm with deionized water to collect the precipitate, and this process was repeated until the pH value of the supernatant was close to 7.0. Finally, Ti was obtained by freeze drying for 24 h. 3 C 2 T x ;

[0244] 1.2) Ti 3 C 2 T x @NiFe 2 O 4 Synthesis: Ti 3 C 2 T x and NiFe 2 O 4 Ti was synthesized by hydrothermal reaction at a mass ratio of 0.3:1 3 C 2 T x @NiFe 2 O 4 , specifically:

[0245] 1.2.1) Weigh 0.15g Ti according to the proportion 3 C 2 Tx Ultrasonic dispersion into 60 ml of deionized water to form a uniform solution;

[0246] 1.2.2) 0.797 g nickel nitrate hexahydrate, 2.21 g ferric nitrate nonahydrate and 0.328 g glucose were weighed in proportion and added to the above solution, stirred at 300 rpm for 10 minutes, and after mixing evenly, transferred to a polytetrafluoroethylene-lined autoclave and kept at 180°C for 15 hours, washed with deionized water and ethanol several times, and vacuum dried at 60°C for 12 hours;

[0247] 2) Synthesis of polyurethane matrix: polyethylene adipate, isophorone diisocyanate, and 4,4'-diaminodiphenyl disulfide were weighed in a molar ratio of 1:1.75:0.75. The specific operation steps are as follows:

[0248] 2.1) Add 5 g of polyethylene adipate into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture;

[0249] 2.2) Cool down to 70°C, add 5 ml of dimethylformamide, 0.97 g of isophorone diisocyanate and 0.5 ml of tetrabutyltin into a three-necked flask, and stir at 300 rpm for 3 hours;

[0250] 2.3) Raise the temperature to 80°C, dissolve 0.47 g of 4,4'-diaminodiphenyl disulfide in 3 ml of dimethylformamide, treat with ultrasound for 10 minutes, then add dropwise to the three-necked flask, and continue stirring at 300 rpm for 3 hours;

[0251] 3) Preparation of self-repairing noise reduction and anti-corrosion coating: According to Ti 3 C 2 T x @NiFe 2 O 4 The mass ratio of Ti to polyurethane matrix is ​​0.05:1. 3 C 2 T x @NiFe 2 O 4 Add to the above polyurethane system and stir with a mechanical stirrer for 0.5 hours;

[0252] 4) The self-repairing anti-corrosion coating synthesized above is coated on the surface of a Q235 carbon steel electrode, cured at 60°C for 12 hours, and cooled to ambient temperature to finally obtain an anti-corrosion organic coating electrode.

[0253] The performance of the organic coating obtained above was tested:

[0254] The electrochemical impedance spectroscopy test results of the coating-modified electrode after immersion for 60 days are as follows: Fig.13 , Fig.14 and Fig.15 As shown in the Nyquist comparison diagram of the original coating, the coating repaired once, and the coating repaired five times, it can be seen that the three curves are all semicircular above the real axis. The coating that has undergone five scratch-healing cycles has a |Z| 0.01Hz Still at 10 9 Ωcm 2 The above results prove that the coating has good long-term protective effect on Q235 carbon steel.

[0255] The coating exhibits good noise reduction effect at room temperature, e.g. Fig.16 As shown in the figure, in the laboratory test, the ambient noise is 95dB, and the coating can reduce the sound pressure to below 60dB, proving that the coating has a good noise reduction effect. In addition, the noise reduction ability of the coating after healing once and five times was tested, as shown in the figure. Fig.17 As shown, there is almost no difference in performance with the complete coating, indicating that the self-healing process does not have a significant impact on the performance of the coating.

[0256] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0257] The above description of the disclosed embodiments enables one skilled in the art to make or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A Ti3C2T x @NiFe2O4 and its preparation method of self-repairing noise reduction and anti-corrosion coating, characterized in that: The coating is composed of Ti3C2T x @NiFe2O4 and polyurethane matrix are mixed in a mass ratio of 0.01-0.05:1; Among them, Ti3C2T x @NiFe2O4 has a sandwich structure consisting of Ti3C2T x and NiFe2O4 in a mass ratio of 0.1-0.5:1; The polyurethane matrix is ​​prepared by addition polymerization of polyester diol, diisocyanate and disulfide in a molar ratio of 1:1.25-2:0.25-1.

2. A Ti3C2T according to claim 1 x @NiFe2O4 and its preparation method of self-repairing noise reduction and anti-corrosion coating, characterized in that: The Ti3C2T x @NiFe2O4 is 1-Ti3C2T x @NiFe2O4、3-Ti3C2T x @NiFe2O4、5-Ti3C2T x @Any one of NiFe2O4.

3. Ti3C2T according to claim 1 x @NiFe2O4 and its preparation method of self-repairing noise reduction and anti-corrosion coating, characterized in that: The polyurethane matrix comprises: The polyester diol is selected from any one or more of polybutylene adipate, polyethylene adipate, polycarbonate diol and polycaprolactone diol; The diisocyanate is selected from any one or more of toluene diisocyanate, isophorone diisocyanate, hexanediol diisocyanate, dicyclohexylmethane diisocyanate, diphenylmethane diisocyanate, and hexamethylene diisocyanate; The disulfide is selected from any one or more of bis(2-hydroxyethyl) disulfide, bis(10-hydroxydecyl) disulfide, 4,4'-diaminodiphenyl disulfide, bis(11-hydroxyundecyl) disulfide, bis(4-(hydroxymethyl)phenyl) disulfide, and diallyl disulfide; The solvent is selected from any one of tetrahydrofuran, acetone, dichloromethane, toluene, dimethylformamide, ether, and dimethylacetamide; The catalyst is selected from any one of dibutyltin dilaurate, dibutyltin, tetrabutyltin, stannous octoate and tributyltin chloride.

4. A Ti3C2T according to claim 1-3 x @NiFe2O4 and its self-repairing noise reduction and anti-corrosion coating preparation method, characterized in that, The specific implementation steps are as follows: 1) Ti3C2T x @NiFe2O4 synthesis: Ti3C2T x Ti3C2T is synthesized with NiFe2O4 in a mass ratio of 0.1-0.5:

1. x @NiFe2O4 composite material, the order is: 1.1) Ti3C2T x Synthesis: Ti3C2T was synthesized by acid etching x , the order is: 1.1.1) Add 1.5 g lithium fluoride to 20 ml hydrochloric acid solution and stir at room temperature at a speed of 200-800 rpm for 10-30 minutes; 1.1.2) Slowly add 1g Ti3AlC2 powder to the above solution in a 40℃ water bath and stir continuously for 24-72 hours; 1.1.3) The reaction solution was centrifuged at 3500 rpm with deionized water to collect the precipitate, and this process was repeated until the pH value of the supernatant was close to 7.

0. Finally, Ti3C2T x ; 1.2) Ti3C2T x @NiFe2O4 synthesis: Ti3C2T x and NiFe2O4 in a mass ratio of 0.1-0.5:1 to synthesize Ti3C2T x @NiFe2O4, specifically: 1.2.1) Weigh Ti3C2T in proportion x Ultrasonic dispersion into 60 ml of deionized water to form a uniform solution; 1.2.2) Weigh nickel nitrate hexahydrate, ferric nitrate nonahydrate and glucose in proportion and add them to the above solution, stir at a speed of 200-800 rpm for 5-30 minutes, transfer to a polytetrafluoroethylene-lined autoclave and keep it in a temperature range of 140-200°C for 9-18 hours, wash it with deionized water and ethanol several times, and vacuum dry it at 60°C for 12 hours; 2) Synthesis of polyurethane matrix: Weigh polyester diol, diisocyanate and disulfide in a molar ratio of 1:1.25-2:0.25-1. The specific operation steps are as follows: 2.1) Add polyester diol into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture; 2.2) Cool down to 70°C, add the solvent, diisocyanate and catalyst dropwise into the three-necked flask, and stir at 300-800 rpm for 1-3 hours; 2.3) Raise the temperature to 80°C, dissolve the disulfide in the solvent, ultrasonicate for 5-10 minutes, then add dropwise to the three-necked flask, and continue stirring at 300-800 rpm for 3-6 hours; 3) Preparation of self-repairing noise reduction and anti-corrosion coating: According to Ti3C2T x @NiFe2O4 and polyurethane matrix mass ratio is 0.01-0.05:1, Ti3C2T x @NiFe2O4 is added into the above polyurethane system and stirred with a mechanical stirrer for 0.5-2 hours.

5. A Ti3C2T x @NiFe2O4 and its self-repairing noise reduction and anti-corrosion coating, characterized in that, The self-repairing noise reduction and anti-corrosion coating synthesized in claim 4 is coated on a metal substrate, cured at 60° C. for 12-24 hours, and cooled to ambient temperature to finally obtain an anti-corrosion organic coating having excellent noise reduction, anti-corrosion and self-repairing properties.